List of reviewers - Vrček, Neven (Journal of Information and Organizational Sciences, 2013)
Jasminka Dobša University of Zagreb, Croatia Kornelije Rabuzin University of Zagreb, Croatia Ali Koyuncugil Capital Markets Board of Turkey, Turkey Ivan Magdalenic University of Zagreb, Croatia Kresimir Fertalj University of Zagreb, Croatia Markus Schatten University of Zagreb, Croatia Dmitri Viattchenin United Institute of Informatics Problems of the NAS of Belarus, Belarus C. Hurt University of Wisconsin, USA Vesna Čančer University of Maribor, Slovenia Zeljka Mihajlovic University of Zagreb, Croatia Renata Mekovec University of Zagreb, Croatia Alen Lovrenčić University of Zagreb, Croatia